RESPONSIFITAS VARIETAS UNGGUL BARU TEBU MASAK AWAL TERHADAP PEMUPUKAN - Mala Murianingrum; Djumali Busro; Prima Diarini Riajaya (BERITA BIOLOGI, 2020)
More than 40% of the potential gap of varieties of sugarcane with actual results in the field is one of the causes of sugar self-sufficiency in Indonesia which has not been reached. The limited knowledge about the responsiveness of  early maturity sugarcane varieties to ferlization is one of the factors causing the large gap. The study aims to determine the responsiveness of new superior early maturity sugarcane varieties conducted in Janti Village, Kediri during July 2018 – August 2019. The study was arranged in a split plot design and repeated 3 times. The main plot consists of 5 fertilizing doses (0.9; 1.0; 1.1; 1.2, and 1.3 times the recommended dose). The subplots consists of 6 new varieties of early maturity sugarcane (MLG 5, MLG 9, MLG 14, PSMLG 2, PSMLG 1, and PS 881). Regression analysis is used to determine the form of response. The optimum dose was determined using the first derivative for closed quadratic equations and was determined > 1.3 times for positive linear equations. Varieties were grouped based on their optimum dose into five groups (no response, little response, sufficient response, more response, and very responsive). The results showed that the MLG 5, PSMLG 1, and PS 881 were classified as sufficient response, while MLG 9, MLG 14, and PSMLG 2 were classified as very responsive to fertilization.